Optimalisasi Keterampilan Operator Terminal Peti Kemas di Pelabuhan Makassar - Paulus Banto; Ratno (Politeknik Pelayaran Barombong, 2020)
Optimizing the Skills of Container Terminal Operators from dock ships must have a certificate obtained through training. A certified loading and unloading equipment operator plays an important role in preventing possible accidents in the operation of loading and unloading equipment, because the operator knows and understands safe operational procedures. the skill of loading and unloading equipment operators, the research was carried out at the Soekarno-Hatta Makassar port, precisely at the Container Terminal. Sources of data obtained by means of observation, direct interviews with operators and literacy related to loading and unloading operators. based on the results of research on operator skills at the container terminal so that human resources are able to improve skills, good cooperation and coordination between parties, and pay attention to loading and unloading operational times in accordance with conditions